2009
DOI: 10.1186/1471-2334-9-126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of a commercially available multiplex PCR system for rapid detection of pathogens in patients with presumed sepsis

Abstract: BackgroundTimely identification of pathogens is crucial to minimize mortality in patients with severe infections. Detection of bacterial and fungal pathogens in blood by nucleic acid amplification promises to yield results faster than blood cultures (BC). We analyzed the clinical impact of a commercially available multiplex PCR system in patients with suspected sepsis.MethodsBlood samples from patients with presumed sepsis were cultured with the Bactec 9240™ system (Becton Dickinson, Heidelberg, Germany) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
106
3
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 13 publications
9
106
3
4
Order By: Relevance
“…17,19 According to previous studies, the use of PCR diagnostic techniques such as SeptiFast could help increase this percentage significantly. 10,11,20,21 In this study, we observed that blood cultures that showed growth were obtained in only 28.6% of the evaluated patients, which is largely consistent with the findings reported for other studies. 18 In comparison with SeptiFast, blood culture showed moderate sensitivity at 72 hours (53.7%); however, this sensitivity is higher than that observed in similar studies.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…17,19 According to previous studies, the use of PCR diagnostic techniques such as SeptiFast could help increase this percentage significantly. 10,11,20,21 In this study, we observed that blood cultures that showed growth were obtained in only 28.6% of the evaluated patients, which is largely consistent with the findings reported for other studies. 18 In comparison with SeptiFast, blood culture showed moderate sensitivity at 72 hours (53.7%); however, this sensitivity is higher than that observed in similar studies.…”
Section: Discussionsupporting
confidence: 81%
“…8 The LightCycler SeptiFast Test (SeptiFast, Roche Diagnostics) is a multipathogen probe-based real-time polymerase chain reaction (PCR) system targeting DNA sequences of bacteria and fungi in blood samples, and it is considered to be a potentially valuable complementary tool in the management of patients with suspected sepsis. [9][10][11] However, the superiority of the SeptiFast system to blood culture for identifying pathogens in sepsis remains unclear. A recently published meta-analysis 12 of 34 studies with a total of 6012 patients showed suboptimal sensitivity of SeptiFast.…”
mentioning
confidence: 99%
“…This is comparable to the results of some earlier studies [26,27]. In studies performed in emergency departments, the rates of positivity were generally higher.…”
Section: Streptococcus Constellatussupporting
confidence: 89%
“…This commercial real-time PCR assay detects 25 bacterial and fungal species or genera that account for [90% of bloodstream pathogens [7]. Observational studies comparing its accuracy to blood culture have indicated a sensitivity ranging between 60 and 95% and specificity between 74 and 83% in hemato-oncology, emergency and critical care settings [9][10][11][12]. PCR took a reported median time of 7-18 h from sampling to result.…”
mentioning
confidence: 99%
“…In these studies, many febrile episodes were associated with pathogen DNAemia detected by PCR but not by blood culture. Many of these ''false-positive'' PCR results were deemed clinically significant, based on retrospective patient chart review or subsequent isolation of the pathogen from relevant clinical samples [9][10][11][12].…”
mentioning
confidence: 99%